Persepsi Mahasiswa Mengenai Pelaksanaan Layanan Pendidikan Mata Kuliah Pendidikan Agama Islam di FMIPA Unikaltar Tahun Akademik 2021/2022 - Abdul Arif; Ratna Dwi Christyanti (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The Faculty of Mathematics and Natural Sciences (FMIPA) of the University of East Kalimantan (Unikaltar) consistently conducts satisfaction surveys to improve the quality of services provided to students. This survey aims to evaluate the performance of each work unit, including lecturers, with the hope that the results obtained can identify aspects that are still hampering or suboptimal. The survey results serve as the basis for formulating steps to improve and enhance the quality of educational services within the faculty. This study specifically highlights the level of student satisfaction with the performance of lecturers in the Islamic Religious Education course. The survey implementation process includes several stages, starting from data collection using a survey instrument, the data input process, and testing the validity and reliability of the instrument to ensure data reliability. Next, the collected data is processed and analyzed to obtain an objective picture of student perceptions. Based on the analysis, the student satisfaction index value obtained is 3.16. This figure is in the "Good" or "Satisfied" category, indicating that students are generally satisfied with the service and learning process carried out by lecturers in the course. These findings provide important input for the institution in maintaining and improving the quality of learning, particularly in the field of religious studies. In the future, it is hoped that similar surveys can continue to be carried out periodically so that the service improvement process can run continuously.